Causes of high variance in building conservation tenders in Malaysia. Issue 2 (9th May 2016) - Yoke Mui, Lim; Ahmad, Yahaya; Nabavi, Faezeh
Abstract : Purpose: – The purpose of this paper is to identify the reasons for the variance among tenders for conservation projects in Malaysia. Design/methodology/approach: – Semi-structured interview approach was adopted because this method allows for effective probing of issues. The interviews are conducted with experienced conservation contractors. The interviews are transcribed and the data are analysed using thematic analysis. Coefficient of variation (CV) measure was also used to determine the level of variance that occurs in tenders for conservation projects. Findings: – The study found that contractors faced difficulty in pricing competitively due to the following four factors, namely, uncertain information on the actual work on site, inexperience in conservation construction works, information in the bill of quantities is incomplete and uncertain labour and material cost. The study of 22 tenders also ascertains that there is a high variance among the tenderers for building conservation projects. This is determined by the CV analysis where conservation works has a mean CV of 25.5 per cent as compared to 6.5 per cent for new build works. Research limitations/implications: – While the interviews managed to draw out insights into the reasons for the high variance among the tender amounts, a definitive conclusion cannot be drawn on the level of variance in tendering for conservation projects due to the limited data that is available for analysis. Originality/value: – The paper offers an insight into the reasons why tenders for conservation projects usually have a higher variance than the norm.